2007
DOI: 10.1227/01.neu.0000255347.25959.d0
|View full text |Cite
|
Sign up to set email alerts
|

Embolization Before Radiosurgery Reduces the Obliteration Rate of Arteriovenous Malformations

Abstract: Embolization before radiosurgery significantly decreases the obliteration rate, even in AVMs with the same volume, location, and marginal dose. Although an excellent outcome rate was higher in the group without embolization, this was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(77 citation statements)
references
References 51 publications
3
67
5
2
Order By: Relevance
“…iv) However, more recent data from multiple centers suggests that embolization before radiosurgery reduces the obliteration rate of AVMs. [233][234][235] (1) Possible mechanisms: (a) Radio-opaque embolic material may reduce the delivered radiation dose. 236 (i) On the other hand, an in-vitro study calculating dose in the presence of either glue or Onyx showed <0.01 -0.2% reduction in dose to the AVM when using the high-energy cobalt source.…”
Section: Embolization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…iv) However, more recent data from multiple centers suggests that embolization before radiosurgery reduces the obliteration rate of AVMs. [233][234][235] (1) Possible mechanisms: (a) Radio-opaque embolic material may reduce the delivered radiation dose. 236 (i) On the other hand, an in-vitro study calculating dose in the presence of either glue or Onyx showed <0.01 -0.2% reduction in dose to the AVM when using the high-energy cobalt source.…”
Section: Embolization Resultsmentioning
confidence: 99%
“…Although Onyx was originally conceived of as an embolic agent for intracranial aneurysms, somewhat disappointing results in a North American randomized trial of the material for aneurysms 212 were followed by encouraging initial results with the use of the agent for the treatment of AVMs. 213 Onyx received FDA approval for presurgical embolization of AVMs in 2005.…”
Section: A Brief History Of Embolization Of Intracranial Avmsmentioning
confidence: 99%
“…The detrimental effects of prior embolization on radiosurgical obliteration rates have been previously reported [14,15,39,40,41,42,43,44,45,46]. Several mechanisms by which embolization reduces radiosurgical obliteration have been postulated, including dose attenuation by embolic agents, increased difficulty in targeting an embolized nidus, post-embolization recanalization, and embolization-induced angiogenesis, although none are yet to be widely accepted as the principal etiology of this widely reported phenomenon [41,47,48,49,50]. Therefore, based on the available preclinical and clinical studies, the effect of prior embolization on post-radiosurgery AVM obliteration rates remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reduced obliteration rate was found if only reduction in flow instead of permanent reduction in nidus volume had been achieved [31]. In 2012, Kano et al [32] reported on 120 patients treated at the University of Pittsburgh with embolization prior to SRS, which showed a reduced rate of obliteration as compared to those patients undergoing SRS alone.…”
Section: Discussionmentioning
confidence: 99%